Implementasi Metode Gergaji dalam Meningkatkan Kemampuan Membaca Al-Qur’an melalui Pendekatan Tartila pada Siswa Sekolah Dasar - Sa’adah, Khoridatus; Ma'ruf, Ahmad (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to determine the implementation of the jigsaw method in developing students' Qur'an reading skills through the Tartila approach at SDN Sukorejo 1. The research method used is a descriptive qualitative approach with data collection techniques in the form of observation, interviews, documentation, and Qur'an reading ability tests. The subjects of the study consisted of 25 fifth grade students. The results of the study showed that the gradual application of the jigsaw technique was able to improve students' Qur'an reading skills, both in terms of tajwid accuracy, letter makhraj, and reading fluency. The collaborative learning process makes students more active, confident, and helps each other in understanding the reading of the Qur'an according to the Tartila rules. From the post-test results, it can be seen that 72% of students showed a significant increase in reading ability. This study recommends the use of the jigsaw method as an alternative strategy for learning the Qur'an in elementary schools that is effective and enjoyable